2020
DOI: 10.1111/pai.13261
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and large local reactions during subcutaneous grass pollen immunotherapy in children

Abstract: Background Subcutaneous immunotherapy (SCIT) is the allergen‐specific curative treatment of allergic rhinitis. Adverse effects, most of which are local, can be observed during the immunotherapy. These adverse effects have been reported more frequently during the pollen season. The purpose of this study was to estimate the rate of local, large local, and systemic reactions during the treatment, to determine the relationship between adverse reactions and the season in which these reactions occur, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Adverse reactions were also reported in several studies as a reason for drop-outs in 3.9 to −11% of drop-outs [18,21]. Systemic reactions were also one of the leading reasons for drop-out (14.3%) in the present study although it was not reported frequently in our center previously [22,23]. In contrast to literature, the cost of SCIT was not a reason for drop-out in the present study, most likely because it is paid for social security system of our country.…”
Section: Discussionsupporting
confidence: 55%
“…Adverse reactions were also reported in several studies as a reason for drop-outs in 3.9 to −11% of drop-outs [18,21]. Systemic reactions were also one of the leading reasons for drop-out (14.3%) in the present study although it was not reported frequently in our center previously [22,23]. In contrast to literature, the cost of SCIT was not a reason for drop-out in the present study, most likely because it is paid for social security system of our country.…”
Section: Discussionsupporting
confidence: 55%
“…Adverse reactions were also reported in several studies as a reason for drop-outs in 3,9% to -11% of drop-outs 19,21 . Systemic reactions were also one of the leading reasons for drop-out (14,3%) in the present study although it was not reported frequently in our center previously 22,23 (24). In contrast to literature, cost was not a reason for drop-out in the present study as AIT treatment is covered by social security system of our country.…”
Section: Discussionmentioning
confidence: 45%
“…Sánchez-Borges et al (20) stated that accelerated build up protocols in cluster immunotherapy are risk factors for systemic reactions. In another study, it was reported that local reactions were more frequent in the build-up phase in pediatric patients who underwent grass pollen immunotherapy, and systemic reactions were observed more frequently in the maintenance phase, although not statistically significant (21). In the current study, when large local and systemic reactions are considered separately, no differences could be noted between build-up and maintenance phases, while the total number of adverse events were significantly higher during the build-up phase as compared to the maintenance phase.…”
Section: Discussionmentioning
confidence: 89%